PENGEMBANGAN HIGHER ORDER THINKING SKILLS DALAM PEMBELAJARAN MATEMATIKA DI SMP - Rafiq Badjeber; Jayanti Putri Purwaningrum (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2018)
21st century mathematical learning emphasizes the importance of developing creativity, critical thinking, cooperation and communication skills. The aims of Mathematics are to trained students to think critically, systematically, logically, analytically, and creatively and have an effective willingness to work which is a Higher Order Thinking Skills. The development of Higher Order Thinking Skills (HOTS) in learning is one manifestation of the implementation of the 2013 curriculum, so that learning and evaluation activities carried out should be oriented to HOTS. HOTS especially in mathematics was born from a continuous process and not only results oriented. A continuous and consistent process is needed to train and familiarize students. This should start from the beginning of the learning activities to take place until the completion of even the process of reflection and evaluation. Teachers must be able to facilitate students to become good thinkers and problem solvers